2020
DOI: 10.1111/caim.12398
|View full text |Cite
|
Sign up to set email alerts
|

How to face the unexpected: Identification and leadership in managing bricolage

Abstract: Drawing on identity theory, empowering leadership, and justice, this study investigates the link between organizational identification and bricolage, and the moderating role of leader's empowering style and interactional justice. Data were collected through a survey on 231 individuals in a media production company. Results supported the research model, illustrating that organizational identification positively predicts individual bricolage, and that the support from the leader, in the form of empowerment and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 145 publications
(294 reference statements)
0
6
0
Order By: Relevance
“…Most studies involving organizational identification are based on Social Identity Theory (SIT; Wu et al, 2016 ; Paolino, 2020 ). And this study uses Social Exchange Theory (SET) to study organizational identification, which is an extension of the application of the theoretical basis of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies involving organizational identification are based on Social Identity Theory (SIT; Wu et al, 2016 ; Paolino, 2020 ). And this study uses Social Exchange Theory (SET) to study organizational identification, which is an extension of the application of the theoretical basis of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Second, shared leadership enables NVTMT members to participate in the decision-making process, which helps them understand entrepreneurial goals, thereby increasing their organisational identity (Dutton et al, 1994). Executives with a high sense of identity are more likely to take on tasks outside of their responsibilities, break away from conventional and integrated roles and methods, and make use of the existing resources in unconventional ways, which promotes entrepreneurial bricolage (Paolino, 2020). Third, shared leadership is accompanied by many team interactions, and the continuous interaction mode and shared values can enhance NVTMT members' confidence in team execution capabilities (Neck et al, 2006).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Research on entrepreneurial opportunities has confirmed the positive impact of leadership on the recognition and exploitation of opportunities for new ventures (Chen, 2007;Koryak et al, 2015). Paolino (2020) also emphasises the importance of leadership in supporting bricolage behaviours in the workplace. However, the literature has not addressed how NVTMT shared leadership affects strategic performance via opportunity recognition and entrepreneurial bricolage.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Recently, some researchers in the field of innovation management have reconciled both approaches and argued for the importance of social F I G U R E 2 Coactive power and cross-cutting identities processes for creativity, which emphasizes the role of group identification mechanisms (e.g., Dosi et al, 2020;Schweisfurth & Raasch, 2020). However, the social identity approach to creativity is mainly supported by experimental studies (Haslam et al, 2013), and the particular context of organizations, which enables the coexistence of different identities, has been overlooked (Paolino, 2020). We bring another perspective on intergroup dynamics by considering them beyond organizational boundaries (i.e., the external audiences) and suggesting that they are impacted by a shift in identities across contexts.…”
Section: Cross-cutting Identities Triggered By Powermentioning
confidence: 99%